2002
DOI: 10.1046/j.1442-2042.2002.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal oncocytomatosis in a long‐term hemodialysis patient treated by laparoscopic surgery

Abstract: A 50-year-old female, who had been on maintenance hemodialysis for 22 years, consulted our clinic because of a left renal mass detected incidentally by ultrasonography. Computed tomography (CT) demonstrated a solid hypervascular mass, suggesting a renal cell carcinoma (RCC), in the left atrophic kidney. Left hand-assisted laparoscopic nephrectomy (HALN) was performed. The histopathological diagnosis was renal oncocytomatosis. Renal oncocytomatosis in a long-term hemodialysis patient is extremely rare. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The previously reported cases are summarized in Table 2 2,3,8,11–16 . The ages of the patients ranged between 12 and 76 years old (mean 55.5 years old).…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported cases are summarized in Table 2 2,3,8,11–16 . The ages of the patients ranged between 12 and 76 years old (mean 55.5 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Esta es una entidad descrita en 1982 por Warfel and Eble 22 , que encontraron más de doscientos focos de oncocitoma en un paciente, de manera bilateral. Desde entonces se han descrito muy escasos casos similares, alguno de ellos de forma unilateral y otros, al igual que en el nuestro, en pacientes sometidos a diálisis durante largo tiempo [23][24][25] . Para algunos autores esta entidad podría entenderse como el paso siguiente a una hiperplasia oncocítica nodular multifocal de asiento renal.…”
Section: Discusionunclassified
“…In the November 2002 issue of the International Journal of Urology , Shiga et al . reported a case of renal oncocytomatosis in a long‐term hemodialysis patient treated by laparoscopic surgery 1 . The authors concluded that the tumor was oncocytoma because the tumor cells were slightly stained with Hale's colloidal iron 1 .…”
mentioning
confidence: 99%
“…reported a case of renal oncocytomatosis in a long‐term hemodialysis patient treated by laparoscopic surgery 1 . The authors concluded that the tumor was oncocytoma because the tumor cells were slightly stained with Hale's colloidal iron 1 . However, the illustration of the tumor shown in their article corresponds to the eosinophilic variant of chromophobe renal cell carcinoma (RCC) because of the compact structure of the tumor cells, the perinuclear halo and the thick cell border 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation